Multichannel Photon Counting Lidar Measurements Using USB-based Digital Storage Oscilloscope - Trung, Dinh-V -; Nguyen, Thanh Binh; Dao, Duy Thang; Bui, Van Hai; Nguyen, Xuan Tu; Pham, Minh Tien; Truong, Phuong Dung; Nguyen, T. T. Bao (Communications in Physics, 2019)
We present a simple method of making multichannel photon counting measurements of weak lidar signal from large ranges, using commonly available USB-based digital storage oscilloscopes. The single photon pulses from compact photomultiplier tubes are amplified and stretched so that the pulses are large and broad enough to be sampled efficiently by the USB oscilloscopes. A software interface written in Labview is then used to count the number of photon pulses in each of the prescribed time bins to form the histogram of LIDAR signal. This method presents a flexible alternative to the modular multichannel scalers and facilitate the development of sensitive lidar systems